Pengaruh Tingkat Pendidikan, Pemahaman Akuntansi, dan Penerapan Akuntansi Terhadap Laporan Keuangan UMKM (Studi Kasus UMKM Tangerang Selatan) - Sari, Anggun Puspita; Fitriawati, Roza (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine the influence of education level, understanding of accounting and application of accounting on MSME financial reports. This research includes field research. The sample used in this research was 40 small entrepreneurs in South Tangerang. Sampling technique with saturated samples. Data collection techniques use questionnaires and direct observation. The data analysis technique used is multiple regression analysis. With the help of the SPSS v.22 application program. The results of the research show that the level of education and understanding of accounting have an influence on the financial reports of SMEs, while the application of accounting has no influence on the financial reports of umkms.